FREQUENCY OF BONE EROSION ON COMPUTERIZED TOMOGRAPGHY SCAN IN ALLERGIC FUNGAL RHINOSINUSITIS - Ali, Muhammad; Attiq, Saima; Raza, Sayed Nusrat; Hakim, Abdul; Ahmed, Shakeel; Ali, Shaukat; Akbar, Farhan; Abbas, Syed Waqar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To analyze the frequency and sites of bone erosion on computerized tomograghy scan in Allergic Fungal Rhinosinustis in Pakistan. Study Design: Retrospective observational study. Place and Duration of Study: Department of ENT, Combined Military Hospital Lahore, Malir Karachi and Rawalpindi, from Jan 2010 to Dec 2019. Methodology: Total 230 cases of Allergic Fungal Rhinosinusitis were screened, out of which 85 patients having bone erosions on computerized tomograpghy scan were included in the study. Bone erosion in different paranasal sinuses and their sub sites were evaluated. Depending upon the number of bone erosion, patients were divided into three categories as mild, moderate and severe. Those having erosion at a single site were labelled as mild, those with two sub sites of erosion as moderate and those with more than two subsites of erosion were labelled as severe cases. Results: Detailed evaluation of computerized tomography scan of paranasal sinuses revealed bone erosion in 85/230 (36.9%) cases. Mean affected age was 23.96 ± 12.71 years. There were 52 (61.1%) males and 33 (38.9%) females. Ethmoid sinus was the most commonly involved sinus to have bone erosions 55 (38.19%) followed by maxillary sinus 38 (26.38%) then sphenoid sinus 27 (18.75%) and lastly frontal sinus 24 (16.6%). Out of 85 patients 48 (56.1%) were having mild, 22 (25.8%) moderate and 15 (17.6%) had severe disease. Conclusion: Allergic Fungal Rhinosinusitis has high frequency of bone erosion. Computerized tomography scan is an important and effective investigation in finding these bony erosions and ethmoid sinus is the.....